THE INFLUENCE OF SELF-SERVICE TECHNOLOGY (SST) AND SERVICE QUALITY TOWARDS REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION (Study on Mcdonald’s Consumer in Semarang) - Nabilah Kinasih; Naili Farida; Ngatno Ngatno (Universitas Diponegoro, 2025)
The ease of access obtained in this era of globalization makes it easier for us to obtain information from one country to another. The tendency of residents in Indonesia to eat at fast food restaurants is considered to have its own social value and prestige, which in turn bring the impression that the image of a luxury with McDonalds being the second most well-liked fast- food restaurant. Repurchase intention is driven by the restaurant's ability to deliver good self-service technology machines and also good service quality which will increase customer satisfaction. However, the level of repeat purchase decisions for McDonalds purchases has decreased. Therefore, this study aims to determine the effect of self-service technology, service quality, and customer satisfaction on the decision to repurchase intention to purchase McDonalds. This study uses a quantitative approach with an explanatory research type. The respondents in this study were McDonalds customers in Semarang with a sample size of 100 respondents calculated using non-probability sampling techniques. The data that has been collected is then processed using SPSS software. The conclusion of this study shows that self-service technology, service quality, and customer satisfaction have a positive effect on the decision to repurchase intention to purchase McDonalds